Mobile app for budget travelling - Seah, Bing Xun (Nanyang Technological University, 2020)
In our daily lives, majority of the people tends to have many things to stress them out such as managing their daily demands from work and family responsibilities which affects them physically and mentally. For instance, they tend to feel depressed and fatigued all the time. Even though it is inevitable, everyone can still take a break from time to time from their daily routine to reduce the stress built up within them and one of the best remedies would be to travel overseas. Travelling overseas helps one’s mind and body to rest, rejuvenate and recharge by exploring and experiencing new things that one would not in their daily lives. However, there are always several circumstances that stop one from doing so such as too busy to plan a trip, budget constraints and safety concerns. This leads to the objective of the project which is to create a travelling mobile application to help resolve all these circumstances.